Hubungan Gaya Hidup Ibu Hamil Dengan Kejadian Preeklamsia Di Wilayah Kerja UPT Puskesmas Turi Lamongan - Lilik Darwati (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: Preeclampsia is one of the causes of maternal and fetal death with a large enough incidence. Many studies have been conducted on pre-eclampsia, but until now the cause of pre-eclampsia has not been determined. Methods: The design of this study used an analytic survey with a cross-sectional approach. The population of this study were all 2nd trimester pregnant women with a total of 33 respondents who checked themselves at the MCH polyclinic at the Turi Health Center, Lamongan Regency. Sampling used the purposive sample method with a total of 30 respondents. The statistical test used in this study was Chi-Square. To test significance, a significance limit of 5% (α = 0.05) was used. The test results said that there was a significant relationship if the p value ≤ α (p≤ 0.05). And the results are said to have no significant relationship if p > α (p > 0.05). Results: Based on the results of the Spearman rank test, there is a relationship between the lifestyle of pregnant women and the incidence of preeclampsia at the KIA polyclinic at the Turi Health Center, Lamongan Regency. The p value = 0.000 where the p value <α 0.05. Then H1 is accepted, which means there is a relationship between the lifestyle of pregnant women and the incidence of preeclampsia at the KIA polyclinic at the Turi Health Center, Lamongan Regency.  Conclusion: the lifestyle of pregnant women is less healthy as many as 15 respondents (50.0%).The incidence of preeclampsia in pregnant women, namely mild preeclampsia, was 16 respondents (53.3%). Spearman's rank test results obtained p value = 0.000 where the p value <α 0.05. Then H1 is accepted, which means there is a relationship between the lifestyle of pregnant women and the incidence of preeclampsia at the KIA polyclinic at the Turi Health Center, Lamongan Regency.